Eksplorasi Fenomena Belajar Sistem Kebut Semalam: Kajian Kualitatif Terhadap Kebiasaan Belajar Siswa Kelas VI - Vera Octavia; Nur Amalia (University of Muhammadiyah Malang, 2023)
Learning and preparing for exams is an essential part of academic life. It requires learning skills and effective time management. However, many students are forced or accustomed to studying at the last minute, which can harm student learning and health. This qualitative phenomenological study aims to explore the phenomenon of learning the overnight speeding system by analyzing and describing the overnight speeding system (SKS) learning strategies for 6th graders in SD SD SDN Trobayan and student perceptions of the SKS strategy. This study also seeks to explore the perspectives of teachers and principals on this phenomenon. This study involved four students, one teacher, and the principal as participants. Data was collected through interviews and document analysis and analyzed using a four-step process: data reduction, analysis, presentation, and drawing conclusions. The results showed that the appropriate credit learning strategy was to re-read the material and make a summary. Although not entirely a lousy learning method, it is necessary to pay attention to the habit of studying fast overnight so that it does not affect the health and performance of students. The scores of students who used the overnight speed study system the night before the test showed successful learning, with an average FCJ score of 801 and a QDNA score of 804, which were higher than the class average of 768.12. The findings of this research can provide teachers and students with insight into how to optimize their study strategies and time management skills, as well as avoid the negative consequences of overnight speeding systems.